THE EFFECT OF USING TIKTOK ON THE SATISFACTION OF LIFE OF LATE ADOLESCENTS - Reski, Reski; Galugu, Nur Saqinah; Nurhayati, Andi (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
The development of internet technology is very  fast, the types of social media are very diverse, one of which is the Tik tok application. The use of the Tiktok application continues to develop. The tiktok application can provide a sense of satisfaction for application users. Where, users of the Tiktok social media feel satisfied when they are in contact with the Tiktok application. This study aims to determine the effect of using Tiktok on the life satisfaction of late teenagers at the University Palopo, to describe what are the effects of using Tiktok on life satisfaction of late adolescents. This research is entitled The effect of using tick marks on life  satisfaction in late teenagers at the University of Palopo in 2023. The research method used for this research is a quantitative method. In this study, data were collected using a questionnaire given to the research sample concerned. before the questionnaire is used, the researcher will first test the measuring instrument by testing the validity and reliability. The results showed that there was an effect of using Tiktok on the life satisfaction of late teenagers, as evidenced by the t count of 57.719> t table; 1,990. In addition, based on the significance value of the coefficients table, the nsig value is obtained. 0.000 <0.05, so it can be concluded that there is an influence that the use of tiktok has a positive effect on the life satisfaction of late teenagers at the University of Palopo in 2023.